IMPLEMENTASI SIKAP KESALEHAN SPIRITUAL DAN SOSIAL PADA MATA KULIAH AL-ISLAM DAN KEMUHAMMADIYAHAN - Milana Abdillah Subarkah; Ety Kurniyati (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2021)
Muhammadiyah higher education is a charitable business that has been successfully developed by Muhammadiyah organizations, as a means of preaching Islam to all Indonesian people. With the holding of Al-Islam and Muhammadiyah courses in each PTM, it is hoped that this can realize Muhammadiyah's ideals, namely, upholding and realizing Islam so that the real Islamic community can be realized. This study tries to provide an overview of the spiritual and social piety attitudes of students who have completed AIK courses by empowering the poor. This research is qualitative research, researchers obtain data from literature studies of book sources, journals, scientific papers, as well as the results of interviews and documentation of empowerment activities for the poor. The results of research on the implementation of spiritual and social piety in Al-Islam and Muhammadiyah subjects include fostering an attitude of being able to read the Koran and its translation, fostering the spirit of practicing the Koran in everyday life, and fostering empathy or caring to others.